Determinação por difração de raios X da estrutura molecular do 1L-1,2,3,4,5-Ciclohexanopentol - (:unkn) unknown (Universidade Estadual de Goiás, 2009)
The cycloalkanes called Cyclitols containing one hydroxyl group connected to at least three carbon atoms in the cycle. These compounds have characteristics of relative and absolute configuration and have attracted the attention of synthetic chemists due to their biological activity and its versatility as synthetic intermediates. Crystallographic study was applied in this work in order to determine the molecular and crystalline structure of the compound of the 1L-1 ,2,3,4,5-Ciclohexanopentol (C6H12O5) with potential biological activity and identify the presence of non-covalent interactions, in special Hydrogen Bonds. The crystal and molecular structure of Cyclitol was determined from data collection X-ray, using the Direct Method and refinement was obtained by the method of Least Squares. The Cyclitol C6H12O5 crystallized in monoclinic crystal system, space group P21, a = 6, 4787 Å, b = 8, 4784 Å, c = 6, 8320 Å, α = γ = 90º, β = 110, 809º, Z = 2 e V = 351, 27 Å3 . Is in its structure at least ten intermolecular interactions of the type O—H···O (Hydrogen Bonds) leading to the formation of a dimer.
Keywords: Cristalografia; Ligação de Hidrogênio; Ciclitóis; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA